2016
DOI: 10.1111/pai.12650
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of atopic diseases and the patterns of sensitization in adolescence

Abstract: The prevalence of rhinoconjunctivitis was high in adolescence. Children with rhinoconjunctivitis with and without comorbidities were frequently sensitized. Children with asthma without concomitant allergic rhinoconjunctivitis were rarely sensitized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 30 publications
9
41
0
Order By: Relevance
“…The same prevalence was reported in the BAMSE study at 12 years of age, and it was 18% at 11 years of age in the Avon Longitudinal Study of Parents and Children . On the other hand, some studies, like the UK Manchester Asthma and Allergy Study and the Odense Adolescence Cohort Study on Atopic Diseases and Dermatitis, reported a higher prevalence of above 30% . Different definitions of current allergic rhinitis can partly account for these differences.…”
Section: Discussionsupporting
confidence: 60%
“…The same prevalence was reported in the BAMSE study at 12 years of age, and it was 18% at 11 years of age in the Avon Longitudinal Study of Parents and Children . On the other hand, some studies, like the UK Manchester Asthma and Allergy Study and the Odense Adolescence Cohort Study on Atopic Diseases and Dermatitis, reported a higher prevalence of above 30% . Different definitions of current allergic rhinitis can partly account for these differences.…”
Section: Discussionsupporting
confidence: 60%
“…Skin sensitization to cow's milk, hen's egg, and peanut at 12 months of age was associated with increased risk of adolescent sensitization and probable FA at 12 and 18 years among subjects from an Australian birth cohort . A collective body of evidence suggests a progression from AD and FA to wheezing, asthma, and sensitization to inhalant allergens at school age . Dietary intake in early life combined with atopy history may have an impact on the risk of developing asthma.…”
Section: Natural Historymentioning
confidence: 98%
“…Of the 190 not participating in the 14-years follow-up investigation significant less were in social class 1–2 and significantly more had mothers who smoked during pregnancy and at birth. A detailed description of the 14 years follow-up investigation was reported earlier [21].
Fig.
…”
Section: Resultsmentioning
confidence: 99%